White Spot Lesions After Orthodontic Treatment: Who Should Treat? - İ. Erhan Gelgör; Tamer Büyükyılmaz (Turkish Journal of Orthodontics, 2007)

(untitled)
The aim of this study was to evaluate alternative treatment methods of the white spot lesions after orthodontic treatment, and also to discuss which department must treat these lesions. Orthodontics or restorative dentistry? BIn general, applications of the microabrasion technique to remove white spot lesions were very effective in the mild and sever lesions but in the deep cavitation lesions composite restorations are inevitable.